Colonization pattern of Cecropia by Azteca ants: Influence of plant ontogeny, environment and host plant choice by queens - Nishi, Aline H. [UNESP]; Romero, Gustavo Q. [UNESP] (My University, 2008)
Several plant species of the large Neotropical genus Cecropia acts as a host plant for ants, especially those of the genus Azteca. Although literature has reported that the Azteca queens found colonies by perforating the prostoma to establish their nests inside the Cecropia trunks (domatia), little is known about which host plant parameters (e.g., ontogenetic development) are evaluated by the queens to choose their hosts, or even whether this choice influences colony success. Because larger plants provide more space and food, it is expected that queens of the plant ant Azteca sp. can more frequently colonize the larger plants of C. pachystachya, and that active colonies, i.e., those with active workers, occur more frequently in these plants. In our study, founding queens occurred more frequently in larger plants. However, linear regressions showed a strong positive relationship between trunk diameter and number of perforated prostomes on young plants yet without active colonies of Azteca sp., indicating that queens colonize plants which are still very young. In these plants several dead and moribund queens were found inside the basal and apical internodes, respectively. Logistic regressions showed that active colonies occurred with higher probability inside the larger plants. These results suggest that queens recognize larger plants, but are not able to evaluate optimal plant sizes suitable for the colony to thrive.
Keywords: Ant-plant mutualism; Cecropia pachystachya; Host plant selection; Ontogeny; Space limitation; Spatial variation